Deterioration of physical performance and cognitive function in rats with short-term high-fat feeding. - Murray, A; Knight, N; Cochlin, L; McAleese, S; Deacon, R; Rawlins, J; Clarke, K (2009)
Efficiency, defined as the amount of work produced for a given amount of oxygen consumed, is a key determinant of endurance capacity, and can be altered by metabolic substrate supply, in that fatty acid oxidation is less efficient than glucose oxidation. It is unclear, however, whether consumption of a high-fat diet would be detrimental or beneficial for endurance capacity, due to purported glycogen-sparing properties. In addition, a high-fat diet over several months leads to cognitive impairment. Here, we tested the hypothesis that short-term ingestion of a high-fat diet (55% kcal from fat) would impair exercise capacity and cognitive function in rats, compared with a control chow diet (7.5% kcal from fat) via mitochondrial uncoupling and energy deprivation. We found that rats ran 35% less far on a treadmill and showed cognitive impairment in a maze test with 9 d of high-fat feeding, with respiratory uncoupling in skeletal muscle mitochondria, associated with increased uncoupling protein (UCP3) levels. Our results suggest that high-fat feeding, even over short periods of time, alters skeletal muscle UCP3 expression, affecting energy production and physical performance. Optimization of nutrition to maximize the efficiency of mitochondrial ATP production could improve energetics in athletes and patients with metabolic abnormalities.